Morro Rock - Albert Walton DeRome:::Creator::::::::::::
Morro Rock in Morro Bay, California. Morro Rock is a 581-foot (177 m) volcanic plug located just offshore from Morro Bay, California, at the entrance to Morro Bay Harbor. Skiffs tied up in forground.